Cambridge checkpoint lower secondary Science grade 7 - Riley, Peter D (United kingdom, Hodder education, 2023)
The Cambridge Checkpoint Lower Secondary Science for Grade 7 is designed for students in the early years of secondary education, typically ages 12-13. This book is aligned with the Cambridge Lower Secondary Science curriculum and provides a comprehensive introduction to key scientific concepts in biology, chemistry, and physics. It aims to develop students' understanding of the world around them and prepares them for the Cambridge Checkpoint assessments.
Keywords: Science : Textbook